Athletes Demonstrate Superior Dynamic Visual Acuity. Issue 7 (July 2021) - Yee, Alan; Thompson, Benjamin; Irving, Elizabeth; Dalton, Kristine
Abstract : SIGNIFICANCE: Athletes exhibit better dynamic visual acuity (DVA) compared with nonathletes, whereas action video game players (VGPs) perform more similarly to controls despite having similar static visual acuity and refractive errors. The differences in DVA between groups were not related to differences in static visual acuity, refractive error, or smooth pursuit gain. PURPOSE: The purpose of the study was to examine whether athletes and VGPs have superior DVA than controls (nonathletes, nongamers). METHODS: Forty-six participants (15 athletes, 11 VGPs, 20 controls) aged 21.7 years (standard deviation, 2.8 years) were recruited. Participants were emmetropic with equivalent monocular and binocular static visual acuity between groups. Dynamic visual acuity was assessed using predictable (horizontal) and unpredictable (random) motion targets at velocities of 5, 10, 20, and 30°/s. Smooth pursuit eye movements were assessed using a horizontal motion step-ramp stimulus at the same speeds. This study was pre-registered with the Center for Open Science (https://osf.io/eu7qc ). RESULTS: At 30°/s, there were significant main effects of group ( F = 4.762, P = .01) and motion type ( F = 9.538, P = .004). Tukey post hoc analysis for groups indicated that athletes performed better than did the control group ( t = −2.919, P < .02). An omnibus (group × motion type × speed) repeated measures ANOVA showed a main effect of speed ( F = 110.137, P < .001) and a speed × motion-type interaction ( F = 27.825, P < .001). Dynamic visual acuity decreased as speed increased, and the slope of the change was greater for random than for horizontal motion. Smooth pursuit gains were not significantly different between groups ( P > .05). CONCLUSIONS: Athletes have superior dynamic visual acuity performance compared with controls at 30°/s. This between-group difference cannot be fully explained by differences in smooth pursuit eye movements and therefore may reflect other differences between the groups.